The effect of popularised foods on social media on adolescents' desire to try - Coşkun, Ayfer Beyaz (Özkan ÖZDEN, 2026)
Adolescents are more sensitive to environmental effects owing to their developmental characteristics and can be easily affected by the content they encounter on social media. This study aimed to investigate the effect of foods that have gained popularity on social media on adolescents’ desire to try them. A questionnaire form including sociodemographic questions, questions about popular food consumption habits, questions about the reason for wanting to try new foods, the social media craving scale and the perception of being affected by social media phenomena scale was applied to 2420 high school students in Elazığ city centre between January 2025 and May 2025 with the necessary permissions. Significant and positive correlations were found between the questions on popular food consumption habits and the scores obtained from the social media craving scale and the scale of perception of being affected by social media phenomena (p<0.05). As the scores obtained from the social media desire scale and the perception of being influenced by social media influencers scale increased, the rate of participants' preference for popular foods also increased. It was concluded that popular foods frequently encountered on social media increase adolescents’ desire to try new foods.
Keywords: Public Health Nutrition; Halk Sağlığı Beslenmesi